A Regulatory Loop Involving Notch and Wnt Signaling Maintains Leukemia Stem Cells in T-Cell Acute Lymphoblastic Leukemia - Zhang, Ling; Wu, Jieying; Feng, Yashu; Khadka, Bijay; Fang, Zhigang; Gu, Jiaming; Tang, Baoqiang; Xiao, Ruozhi; Pan, Guangjin; Liu, Jia-Jun (Frontiers in Cell and Developmental Biology, 2021)
Leukemia-initiating cells play critical role in relapse, resistance to therapies and metastases but the mechanism remains largely elusive. We report that β-catenin is over-expressed in almost all T-ALL patients and flow sorted β-cateninhigh fractions are highly resistant to therapy, leading to liver metastases in nude mice as well as dysregulated lncRNAs. Pharmacological inhibition through XAV-939 as well as si-RNA mediated inhibition of β-catenin is initially effective in re-sensitization to therapy, however, prolonged inhibition shifts dependency from β-catenin to Notch signaling, with particularly high levels of receptors Notch 1 and Notch 2. The results are verifiable in a cohort of T-ALL patients comprising of responders vs. those who have progressed, with β-catenin, Notch 1 and Notch 2 elevated in progressed patients. Further, in patients-derived cells, silencing of Notch 1 or Notch 2 does not counter resistance to β-catenin inhibition, rather pharmacological pan-Notch inhibition is needed to overcome resistance and its effect on in vitro tumor sphere formations as well as in vivo liver metastases. Thus, wnt and Notch signaling are part of a regulatory loop mutually compensating for each other in T-ALL, while ensuring the maintenance of stem cell phenotype.